Empowering Youth and Women Small and Medium Enterprises: A Study on Enhancing Government Loans Operations in Tanzania - Lulamye, Steward Ngagard (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2025)
This study investigated the small and medium enterprises owned by youth and women, which received government loans from a local government authority in Kinondoni Dar es Salaam. Qualitative design was adopted for the study and used focus group discussions as a data collection tool. A total of four focus group discussions were conducted with participants ranging from six to nine. The results showed that Ward Executive Officers and Community Development Officers were sources of loan scheme information. The SMEs group adhered to its formation. The study revealed the suitability of certain business practices and environments. The study identified challenges impeding the development of SMEs, including discouragement from surrounding communities, insufficient business education, inadequate space for business ventures, low purchasing power among customers, competition, and insufficient capital. The study also disclosed that strategies for enhancing government loan operations to better empower youth and women’s SMEs included augmenting the quantity of government loans, lengthening the repayment period, offering subsidies for successful SMEs, conducting regular training for entrepreneurs, and notifying the bank about loan reimbursement. The study concludes that, by empowering youth and women entrepreneurs, Tanzania can strengthen its economy and create more inclusive opportunities for development. The study recommends that the government and all relevant stakeholders enhance the business operations environments to bolster the SMEs established through government loans.